Defect chemistry of electrocatalysts for CO2 reduction - Li, Hongqiang; Li, Ran; Niu, Jiabao; Gan, Kaining; He, Xiaojun (Frontiers in Chemistry, 2022)
Electrocatalytic CO2 reduction is a promising strategy for converting the greenhouse gas CO2 into high value-added products and achieving carbon neutrality. The rational design of electrocatalysts for CO2 reduction is of great significance. Defect chemistry is an important category for enhancing the intrinsic catalytic performance of electrocatalysts. Defect engineering breaks the catalytic inertia inherent in perfect structures by imparting unique electronic structures and physicochemical properties to electrocatalysts, thereby improving catalytic activity. Recently, various defective nanomaterials have been studied and show great potential in electrocatalytic CO2 reduction. There is an urgent need to gain insight into the effect of defects on catalytic performance. Here, we summarized the recent research advances on the design of various types of defects, including carbon-based materials (intrinsic defects, heteroatom doping and single-metal-atom sites) and metal compounds (vacancies, grain boundaries, and lattice defects). The major challenges and prospects of defect chemistry in electrocatalytic CO2 reduction are also proposed. This review is expected to be instructive in the development of defect engineering for CO2 reduction catalysts.